GRANULAR REPRESENTATION OF THE INFORMATION POTENTIAL OF VARIABLES - APPLICATION EXAMPLE - Kiersztyn, Adam; Gandzel, Agnieszka; Celiński, Maciej; Koczan, Leopold (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2021)
With the introduction to the science paradigm of Granular Computing, in particular, information granules, the way of thinking about data has changed gradually. Both specialists and scientists stopped focusing on the single data records themselves, but began to look at the analyzed data in a broader context, closer to the way people think. This kind of knowledge representation is expressed, in particular, in approaches based on linguistic modelling or fuzzy techniques such as fuzzy clustering. Therefore, especially important from the point of view of the methodology of data research, is an attempt to understand their potential as information granules. In this study, we will present special cases of using the innovative method of representing the information potential of variables with the use of information granules. In a series of numerical experiments based on both artificially generated data and ecological data on changes in bird arrival dates in the context of climate change, we demonstrate the effectiveness of the proposed approach using classic, not fuzzy measures building information granules.